Market Integration and Agribusiness Performance in Indonesia - Lasaksi, Pardin (West Science Agro, 2024)
This quantitative study explores the relationship between Indonesian agricultural performance, technological adoption, market integration, and environmental legislation. Data was gathered via a survey of 250 agriculture companies, and structural equation modeling (SEM-PLS) was used for analysis. The findings show a strong correlation between agricultural performance, technology adoption, market integration, and environmental legislation. More specifically, improved productivity, profitability, and sustainability are linked to increasing degrees of market integration, technology adoption, and adherence to environmental regulations. The results highlight the significance of cultivating transparent and competitive markets, encouraging the adoption of contemporary agricultural technologies, and enacting efficacious environmental regulations to augment the competitiveness, sustainability, and adaptability of Indonesia's agribusiness industry.